PENDISTRIBUSIAN ZAKAT BERBENTUK SEMBAKO MELALUI LAZISMU (KL UNIMAR) KEPADA MASYARAKAT SUKU BADUY DI DESA CIBOLEGER KABUPATEN LEBAK - Helmas Septiyo Hadi; Abdul Azis Setiawan; Dadang Dadang; Wahyu Fajar Nugraha; Abu Naim; Sena Atmaja (LPPM Universitas Bina Bangsa, 2023)
In Islamic law, Obligatory charity can be interpreted as a certain amount of certain types of assets that must be given to certain groups, with certain conditions. Obligatory charity must be issued to every reasonable, mature and independent Muslim. LazisMu Muhammadiyah University Service Office A.R. Fachruddin as the holder of full control over obligatory charity, donation and alms lecturers and employees who work within the Muhammadiyah University A.R. Fachruddin has been making efforts to collect zakat which will later be distributed to fellow humans in need, coinciding on Tuesday to Wednesday March 22, 2023 LazisMu KL Muhammadiyah University A.R. Fachruddin distributes zakat, infaq and shadaqah as a result of collection to the Outer Baduy people located in Ciboleger District, Lebak Regency, where the legal reference for giving obligatory charity is that it is permissible or can be given to the needy, poor, converts, amil, riqab, gharimin, fi sabilillah and ibn sabil. Most of the Outer Baduy tribes are converts and do not have good economic strength (poor), so it is very appropriate for LazisMu Muhammadiyah University Service Office A.R. Fachruddin distributes obligatory charity, donation and alms within the Outer Baduy tribe